Latest Results in Charmed Baryons Spectroscopy - Solovieva Elena (EPJ Web of Conferences, 2019)
An overview of recent developments in the spectroscopy of charmed baryons is given. The classification of charmed baryons is presented, a quark model for ground states is briefly described, and the energy levels of excited states are analysed.